A Convenient Synthesis of 1,2,4-Trihalophenothiazine- 3-ones and Their Conversion into (1,4)-Benzothiazino(2,3-b)-Phenothiazines - Ojha, K.G.; Adwani, Purnima; Mathur, Neha (Asian Journal of Chemistry, 2010)
A simple synthesis is reported for (1,4)-benzothiazino (2, 3–b)–phenothiazines. 2-amino–3–(methoxy/nitro)–5–(nitro/methyl) benzenethiols were condensed with chloranil/bromanil and the resulting phenothiazine- 3-ones were further condensed with same or different -amino-benzenethiols to get substituted (1,4)-benzothiazino-(2,3-b)-phenothiazines. Symmetric (1 ,4)-benzothiazino-(2,3-b )-phenothiazines were also prepared by single step reaction involving condensation of substituted 2-aminobenzenethiols with chloranil/bromanil in 2 : 1 molar ratio. Their spectral studies are also included.